2017
DOI: 10.1038/gt.2017.19
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of adeno-associated virus vector-mediated gene transfer to the respiratory tract

Abstract: An efficient adeno-associated virus (AAV) vector was constructed for the treatment of respiratory diseases. AAV serotypes, promoters and routes of administration potentially influencing the efficiency of gene transfer to airway cells were examined in the present study. Among the nine AAV serotypes (AAV1-9) screened in vitro and four serotypes (AAV1, 2, 6, 9) evaluated in vivo, AAV6 showed the strongest transgene expression. As for promoters, the cytomegalovirus (CMV) early enhancer/chicken β-actin (CAG) promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 62 publications
0
16
0
1
Order By: Relevance
“…In our research, we focused on the use of CMV and CAG promoters. The choice of a promoter is extremely important in targeted gene therapy and, thus, in the individualization of treatment (90)(91)(92). We noticed that improved transduction efficiency in melanoma cells in in vitro and in vivo conditions was obtained by the CAG promoter (Figures 3, 7, and 8).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our research, we focused on the use of CMV and CAG promoters. The choice of a promoter is extremely important in targeted gene therapy and, thus, in the individualization of treatment (90)(91)(92). We noticed that improved transduction efficiency in melanoma cells in in vitro and in vivo conditions was obtained by the CAG promoter (Figures 3, 7, and 8).…”
Section: Discussionmentioning
confidence: 93%
“…The expression of CAG promoter in the lungs lasted up to 12 months while that of CMV expression up to 8 months. However, the CMV promoter has an immediate effect that provides strong but short-term expression (90,91). However, it is very susceptible to silencing in some cell types (89).…”
Section: (A and C) Results Show The Transduction Efficiency Of The Ramentioning
confidence: 99%
“…Previous studies indicated that the endogenous mammalian promoters can provide higher expression than viral promoters [26,27]. The EF-1α promoter has been shown to be one of the strongest promoters in various cell lines [28,29]. Indeed, the EF-1α promoter is often active in cells where viral promoters fail to drive downstream gene expression and are gradually silenced [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…These studies exemplify the challenge of developing efficient AAV vectors for evaluation in relevant CF animal models, including pigs [4*], sheep [7], ferrets [8] and mice [6], but also provide efficient transduction of human epithelia for clinical translation. For example, nine naturally occurring AAV serotypes tested in human cells and murine lungs identified AAV6 as the strongest candidate in both human and mouse epithelium [5]. However, other serotypes, including AAV2/5, i.e.…”
Section: Viral Gene Therapy I Adeno Associated Virus (Aav)mentioning
confidence: 99%